2015
DOI: 10.1007/s40279-015-0351-6
|View full text |Cite
|
Sign up to set email alerts
|

Motor Competence and its Effect on Positive Developmental Trajectories of Health

Abstract: In 2008, Stodden and colleagues took a unique developmental approach toward addressing the potential role of motor competence in promoting positive or negative trajectories of physical activity, health-related fitness, and weight status. The conceptual model proposed synergistic relationships among physical activity, motor competence, perceived motor competence, health-related physical fitness, and obesity with associations hypothesized to strengthen over time. At the time the model was proposed, limited evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
1,025
8
61

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 936 publications
(1,148 citation statements)
references
References 113 publications
54
1,025
8
61
Order By: Relevance
“…Motor development is considered an important factor in children's overall health (Hill, 2010;Lubans, Morgan, Cliff, Barnett, & Okely, 2010;Robinson et al, 2015;Stodden et al, 2008). In spite of its significance, a common understanding of the latent construct of motor behavior underlying assessment is lacking.…”
Section: Motor Competence and Related Constructsmentioning
confidence: 99%
“…Motor development is considered an important factor in children's overall health (Hill, 2010;Lubans, Morgan, Cliff, Barnett, & Okely, 2010;Robinson et al, 2015;Stodden et al, 2008). In spite of its significance, a common understanding of the latent construct of motor behavior underlying assessment is lacking.…”
Section: Motor Competence and Related Constructsmentioning
confidence: 99%
“…Motor competence refers to the ability to execute diverse motor tasks in a skilful manner, which includes the coordination of both gross and fine motor skills (Gallahue, Ozmun, & Goodway, 2012;Haga, 2008). The role of motor competence in children's physical activity levels has been conceptualized in a theoretical model by Stodden et al (2008; recently revised by Robinson et al in 2015). Numerous studies have confirmed the proposed positive relationship between children's motor competence and their physical activity levels (e.g., Holfelder & Schott, 2014;Logan et al, 2014;Lubans, Morgan, Cliff, Barnett, & Okely, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still unclear how the development of health-related variables may impact each other to promote either positive or negative trajectories (Robinson et al, 2015). Stodden et al (2008) present a conceptual model proposed synergistic relationships among physical activity, motor competence, physical fitness, and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that an explanation of the relations between these constructs is multifaceted (Robinson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%